Wireless Powering of Internet of Things Devices using Radio Frequency Harvesting - Konter, Isay; Hajian, Mostafa (Student Undergraduate Research E-journal!, 2018)
Internet of Things (IoT) is tagging low power devices, miniaturized, with machine-readable identification tags, which are integrated with sensors to collect information and wireless technology to connect them with the Internet. These devices have a very low energy usage. Powering these devices with battery is very labor intensive, costly and tedious especially as number of nodes increases, which is in many applications, is the case. Hence the main objective of this research is to introduce new product called RF Collector, in the market such that IoT devices function independent of battery. Using the suggested approach they will be energized using Radio Frequency (RF) energy harvesting. RF Collector wirelessly capture the RF energy that is wasted in space, and re-use it again as the power source for IoT devices and hence making them autonomous of battery. The ability to harvest RF energy enables wireless charging of low-power devices in real time. This has resulting benefits to sustainability, cost reduction, product design, usability, and reliability.